A alfabetização e o letramento: olhares da produção acadêmica nacional - Oliveira, Rafaela Luiza Klitzke de (2015)
This article comprises understanding the closeness and the circularity of what is taking place on literacy and lettering in the country, the connection between the researchers and the initial and continuing education processes with the educational institutions. It is about a study, as state of knowledge on and from the literacy and lettering productions, with which seeks to place the relationship between academic research and the ads that nourish the pedagogical practice of literacy teachers. In order to analyze and produce an analytical framework on the national academic research on literacy and lettering, this research brought to contribute towards subsidizing tenders / literacy projects and the initial formation and continuing teachers for this segment of Basic education. By focusing on domestic production via dissertations and theses on literacy and lettering, it sought to explain its main characteristics and contributions, whether literacy and lettering proposals, or even for the teacher training process for this area of expertise. The exercise, in turn, arises from the grouping of production available online in Theses Database Capes, from the selection of some search expressions on the subject. We conclude that, despite the numerous publications on literacy and lettering, researching on this topic is still relevant and necessary, especially for what appears from this production, the perception is that many literacy teacher slack knowledge about the concepts researched and their implications on and for practices and educational processes.